AN ANALYSIS OF THE RELATIONSHIP BETWEEN INTRINSIC MOTIVATION AND EXTRINSIC MOTIVATION FOR EMPLOYEE PERFORMANCE SATISFACTION - Aminah Djunaid (Jurnal Ekonomi, 2023)
This study aims to analyze whether there is a significant difference between work motivation between intrinsic and extrinsic motivation on employee performance satisfaction at the PD Pasar Makassar Raya office. The type of research used is explanatory research with a quantitative approach. The population in this study were 30 employees at the PD Pasar Makassar Raya office. Because the number of employees is too large, some of the population is used as a respondent. Thus, the sampling using the sample method. Data collection methods used are questionnaires, documentation and interviews. Data analysis technique in this study used multiple linear regression analysis by conducting simultaneous and partial variable tests. Data processing using SPSS 22.0 for Windows. The results showed that intrinsic and extrinsic motivation had a positive and significant correlation both partially and simultaneously on performance. It can be concluded that there is a significant relationship between intrinsic and extrinsic motivation on employee performance satisfaction at the PD Pasar Makassar Raya office.